2002
DOI: 10.1056/nejmoa021583
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dialysis Dose and Membrane Flux in Maintenance Hemodialysis

Abstract: Patients undergoing hemodialysis thrice weekly appear to have no major benefit from a higher dialysis dose than that recommended by current U.S. guidelines or from the use of a high-flux membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
1,331
11
41

Year Published

2004
2004
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,684 publications
(1,426 citation statements)
references
References 31 publications
24
1,331
11
41
Order By: Relevance
“…A secondary analysis suggested a benefit of high-flux membranes in those who were on hemodialysis for Ͼ3.7 years. 6 Higher dose was shown to be associated with a trend toward reduction in relative risk of mortality for women but not men; this was found to be nonsignificant after applying the Bonferroni correction for multiple comparisons. 7 Although the HEMO study is a significant landmark in the history of dialysis therapy, several limitations need to be considered while interpreting its results.…”
Section: An Overview Of the Hemo Studymentioning
confidence: 94%
“…A secondary analysis suggested a benefit of high-flux membranes in those who were on hemodialysis for Ͼ3.7 years. 6 Higher dose was shown to be associated with a trend toward reduction in relative risk of mortality for women but not men; this was found to be nonsignificant after applying the Bonferroni correction for multiple comparisons. 7 Although the HEMO study is a significant landmark in the history of dialysis therapy, several limitations need to be considered while interpreting its results.…”
Section: An Overview Of the Hemo Studymentioning
confidence: 94%
“…either for a urea reduction ratio (URR) > 65% or an equilibrated Kt/V urea >1.2, delivered thrice weekly [19,20]. The Hemodialysis (HEMO) Study trial in adults showed no difference in survival between patients with a mean eKt/V of 1.16 and those achieving a Kt/V of 1.53 [30]. These findings are similar to those in a recent study of 613 adolescents on HD, in which hospitalization risk was increased with a single pool Kt/V <1.2 compared to 1.2-1.4 but a spKt/V of >1.4 did not improve outcome [31].…”
Section: Haemodialysismentioning
confidence: 99%
“…In adults, the result of the National Cooperative Dialysis Study showed a survival benefit with increased dialysis prescription [1]. Disappointingly, no survival benefits with further increase in small solutes clearances once a certain threshold level was reached, which were demonstrated in two major adult trials: the Effects of Increased Peritoneal Clearances on Mortality Rates in Peritoneal Dialysis: ADEMEX, a Prospective, Randomized, Controlled Trial (ADEMEX) and the Effect of Dialysis Dose and Membrane Flux in Maintenance Hemodialysis (HEMO) studies [2,3]. However, residual renal clearance as the major predictor of survival in dialysis patients (both hemodialysis and peritoneal dialysis) was demonstrated in carefully conducted re-analyses of both studies [4,5].…”
Section: Introductionmentioning
confidence: 99%